Catalogue of Dacetini and Solenopsidini ant type specimens (Hymenoptera, Formicidae, Myrmicinae) deposited in the Museu de Zoologia da Universidade de São Paulo, Brazil - Ulysséa, Mônica Antunes; Brandão, Carlos R.F. (Papéis Avulsos de Zoologia, 2013)
The present catalogue lists ant (Formicidae) types of the Myrmicinae tribes Dacetini (Acanthognathus and Strumigenys) and Solenopsidini (Allomeurs, Carebarella, Megalomyrmex, Monomorium, Oxyepoecus, Solenopsis, Carebara and Tropidomyrmex) housed in the Formicidae collection of the Laboratório de Hymenoptera, Museu de Zoologia da Universidade de São Paulo/MZSP, Brazil. In total, the collection includes 141 types of these tribes, 41 of the Dacetini (nine holotypes and paratypes, 15 holotypes, 13 paratypes and four syntypes) and 100 of the Solenopsidini (28 holotypes and paratypes, eight holotypes, 29 paratypes, 27 syntypes, four lectotypes and paralectotypes, one lectotype and three paralectotypes), of which 37 and 89 are of still recognized species, respectively. We record label information, condition of the specimens, nomenclatural changes and type status, as well as provide indexes of the listed taxa.